APLIKASI ZAT PENGATUR TUMBUH DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN VEGETATIF, KANDUNGAN VITAMIN C DAN FLAVONOID PADA TANAMAN KELOR MUDA - T Rosmawaty; Sri Mulyani; Yulia Triana Siregar; Weni Purnama Sari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACTThe purpose of this study was to determine the effect of both interaction and primary administration of Growtone ZPT and NASA POC on vegetative growth, Vitamin C content and flavonoids in Young Moringa plants. This research was carried out in the Experimental Garden of the Faculty of Agriculture, Riau Islamic University. This research was conducted for 4 months, from June 2019 to September 2019. This study used a Factorial Complete Randomized Design (RAL) consisting of the first 2 (two) factors (Growtone immersion duration) with a concentration of 50 ppm consisting of 4 (four) levels: L1 (20 minutes), L2 (40 minutes), L3 (60 minutes). The Second Factor (Nasa POC concentration), consists of 4 (four) levels: K0 (without treatment), K1 (2 ml / l water), K2 (4 ml / l water) and K3 (6 ml / l water). Data were analyzed statistically and continued with further tests of Honestly Significant Difference (BNJ) at the 5% level. Based on the results of research that has been conducted concluded that: The interaction of soaking time treatment and the concentration of real Nasa POC on the percentage of growth, number of leaf stalks, fresh leaf weight, number of leaflets. The best treatment was the growtone soaking treatment 40 minutes and the concentration of POC Nasa 6 ml/l water (L2K3). The main effect of growtone soaking time was apparent in all observational parameters. The best treatment is soaking for 40 minutes (L2). The main effect of real Nasa POC concentration on all parameters observed. The best treatment is the concentration of POC Nasa 6 ml/l water (K3). Giving growtone treatment with immersion for 40 minutes and POC NASA concentration by administering 4 ml per liter of water (L2K2) gives the best treatment results on the content of vitamin C,and flavonoids Moringa plants.